DETERMINATION OF FACTORS INFLUENCING DRUG USE USING THE FUZZY AHP METHOD AT THE NORTH SUMATRA PROVINCIAL NATIONAL NARCOTICS AGENCY (BNNP) - Roshihan Mawazzi Lubis; Ismail Husein (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The phenomenon of drug abuse is primarily observed within the population characterized by experimental drug use, with a particular emphasis on individuals who are actively employed. Several factors, such as socioeconomic status and peer influence, have been identified as influential contributors in the occurrence of drug misuse. The objective of this study is to ascertain the determinants that impact individuals engaged in drug usage through the application of the Fuzzy Analytical Hierarchy Process (AHP) technique. The data for this research is derived from internal agencies, which aim to identify the elements that contribute to drug users' susceptibility to addiction and the subsequent development of drug dependency in individuals. The factors included in this study encompass Environment ( ), Family ( ), Economy ( ), Education ( ), and Personality ( ). The utilization of Fuzzy Analytic Hierarchy Process (AHP) for conducting data analysis methodologies. The AHP method yielded a value of λ=8.927, a CI of 2.65, and a CR of 87.39%. Moreover, during the Fuzzy Analytic Hierarchy Process (AHP) phase, it was determined that the primary determinant of drug abuse is  (environment), exhibiting the highest average score of 0.8321, equivalent to 83.21%, in comparison to other components